Predictive validity of ventilatory and lactate thresholds for cycling time trial performance - Amann, M.; Subudhi, A. W.; Foster, C. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Purpose: To determine which laboratory measurement best predicts 40 km cycling time-trial (TT) performance.